INFORMATION-ANALYTICAL LEARNING MANAGEMENT SYSTEM OF UNIVERSITIES - Tryus, Y.; Stetsenko, I.; Herasymenko, I.; Hrytsenko, V. (Journal of Information Technologies in Education (ITE), 2016)
We consider conceptual approaches to creation of information systems, learning management school, which uses modern methods of decision-making and simulational modeling,web-technologies. The main criteria for the selection of development tools of the system are:openness, free of charge, easy to use and independence from system software and hardware. The chosen technology and the system itself satisfies such requirements as: focus on national and international standards in the field of higher education, adherence to service-oriented architecture,ensuring stable operation with a large number of users, support for a clear division of user rights to obtain and change information resources, software modularity the final product and its ability to integrate into the corporate information system of the university.